Systematic Literature Review on the Effectiveness of Multimedia in Flipped Learning Classrooms - Mohamad Syarief Abdullah; Ketut Agustini; I Gde Wawan Sudatha; Anak Agung Adi Wiryya Putra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study addresses a critical gap in flipped learning research by focusing on the specific role of multimedia tools in enhancing student engagement and comprehension—an area often overlooked in prior studies that tend to generalize the benefits of flipped classrooms. Employing a Systematic Literature Review (SLR) methodology, the study adheres to PRISMA guidelines and analyzes 20 empirical studies selected from 147 initial records obtained through databases such as Scopus, Google Scholar, and PubMed. Articles were included based on relevance, publication year (2019–2024), and methodological rigor. The findings quantitatively indicate that 100% of the studies reported improved comprehension, 90% observed heightened engagement, and 80% noted enhanced learning flexibility through multimedia-supported flipped learning. However, 60% of the studies identified infrastructural and digital literacy challenges as significant barriers. Theoretically, this research reinforces Vygotsky’s social constructivism by emphasizing interactive and student-centered learning environments. Practically, it underscores the need for teacher training and robust digital infrastructure to optimize flipped learning implementation. This review contributes actionable insights into designing more adaptive, technology-integrated education systems.